Microstructural characterisation of novel nitride nanostructures using electron microscopy - Severs, J (2014)
Novel semiconductor nanostructures possess a range of notable properties that have the potential to be harnessed in the next generation of optical devices. Electron microscopy is uniquely suited to characterising the complex microstructure, the results of which may be related to the growth conditions and optical properties. This thesis investigates three such novel materials: (1) GaN/InGaN core/shell nanowires, (2) n-GaN/InGaN/p-GaN core/multi-shell microrods and (3) Zn3N2 nanoparticles, all of which were grown at Sharp Laboratories of Europe. GaN nanowires were grown by a Ni-catalysed VLS process and were characterised by various techniques before and after InGaN shells were deposited by MOCVD. The majority of the core wires were found to have the expected wurtzite structure and completely defect free – reflected in the strong strain-free photoluminescence peak –with a- and m- axis orientations identified with shadow imaging. A small component, <5%, were found to have the cubic zinc-blende phase and a high density of planar faults running the length of the wires. The deposited shells were highly polycrystalline, partially attributed to a layer of silicon at the core shell interface identified through FIB lift-out of cross section samples, and accordingly the PL was very broad likely due to recombination at defects and grain boundaries. A high throughput method of identifying the core size indirectly via the catalyst particle EDX signal is described which may be used to link the shell microstructure to core size in further studies. An n-GaN/InGaN/p-GaN shell structure was deposited by MOCVD on the side walls of microrods etched from c-axis GaN film on sapphire, which offers the possibility of achieving non-polar junctions without the issues due to non-uniformity found in nanowires. Threading dislocations within the core related to the initial growth on sapphire were shown to be confined to this region, therefore avoiding any harmful effect on the junction microstructure. The shell defect density showed a surprising relationship to core size with the smaller diameter rods having a high density of unusual 'flag' defects in the junction region whereas the larger diameter sample shells appeared largely defect free, suggesting the geometry of the etched core has an impact on the strain in the shell layers. The structure of unusual 'flag' defects in the m-plane junctions was characterised via diffraction contrast TEM, weak beam and atomic resolution ADF STEM and were shown to consist of a basal plane stacking faults meeting a perfect or partial dislocation loop on a pyramidal plane, the latter likely gliding in to resolve residual strain due to the fault formed during growth. Zn3N2 has the required bandgap energy to be utilised as a phosphor with the additional advantage over conventional materials of its constituent elements not being toxic or scarce. The first successful synthesis of Zn3N2 nanoparticles appropriate to this application was confirmed via SAD, EDX and HRTEM, with software developed to fit experimental polycrystalline diffraction patterns to simulated components suggesting a maximum Zn3N2 composition of ~30%. There was an apparent decrease in crystallinity with decreasing particle size evidenced in radial distribution function studies with the smallest particles appearing completely amorphous in 80kV HRTEM images. A rapid change in the particles under the electron beam was observed, characterised by growth of large grains of Zn3N2 and ZnO which increased with increasing acceleration voltage suggesting knock-on effects driving the change. PL data was consistent with the bandgap of Zn3N2 blue shifted from 1.1eV to around 1.8eV, confirming the potential of the material for application as a phosphor.